S130. REHOSPITALIZATION RATES FOLLOWING EARLY INTERVENTION TREATMENT FOR SERIOUS MENTAL ILLNESS. (9th April 2019) - Warner, Alia; Hamilton, Jane; Allen, Melissa; Lane, Scott
Abstract: Background: Serious mental illnesses (SMI) are associated with impairment across domains and substantial distress. The treatment of SMI comes at a high cost to health care systems, given the chronicity and severity of illness. Relatedly, individuals with SMI have especially high recidivism rates, and within the United States, hospitalization rates and health care costs are increasing. Early interventions that are administered within the first five years of onset of illness are hypothesized to have the strongest influence on the course of illness. The impact of early interventions with low income, uninsured individuals in a safety-net setting are rarely examined, and fewer studies have included participants with SMI other than schizophrenia (e.g., major depressive disorder and bipolar disorder). Rehospitalization rates following inpatient treatment appears of particular import, especially among disadvantaged individuals (i.e. indigent). This study aims to examine rehospitalization rates among patients participating in an early onset treatment program in contrast to a comparison group from the same psychiatric hospital. Methods: Retrospective review identified 165 patients that participated in the Early Onset Treatment Program (EOTP), an inpatient treatment program for individuals in the early stages of serious mental illness. A comparison sample (n = 155) of individuals admitted to the same hospital was utilized, which was matched on gender, age, and primary diagnosis. Rehospitalizations at 6-month and 12-month follow-up after discharge was calculated via chart review. ANOVA was used to compare rehospitalization rates between groups. Results: Among the samples, 60% of the EOTP group and 62.6% of the comparison group had a primary diagnosis of a schizophrenia-spectrum disorder or a major mood disorder with psychotic features. The remaining sample had a primary psychiatric diagnosis of a major mood disorder without psychotic symptoms. Mean length of stay (LOS) for the EOTP group was 58.8 days, while the comparison group had a mean LOS of 8.59 days. For those in the EOTP, 65.4% completed at least 45 of the 90 days of treatment, and 25% received individual therapy in addition to group psychotherapy that all participants received. Rehospitalizations were significantly lower in the EOTP group at 6-month [F(1, 318) = 43.77, p < .001] and 12-month [F(1, 318) = 31.73, p < .001) follow-up. Mean rehospitalizations for the EOTP group were .26 (SD = .62) at 6-months following discharge, and .55 (SD = 1.06) at 12-months. The comparison group had a mean of .78 (SD = 1.08) re-admissions at 6-months, and 1.34 (SD = 1.73) at 12-month follow-up. The presence of psychotic symptoms was not associated with rates of rehospitalization. Discussion: Results provide additional support for the effectiveness of early interventions for SMI, including SMI populations that tend to be excluded from other similar studies. These results also provide support that early treatment reduces rehospitalization among economically disadvantaged individuals, despite additional challenges (e.g., difficulties with housing, finances, social support, and follow-up care). Since early onset interventions are associated with fewer re-admissions, early onset treatment may also assist in reducing health care costs. Further research is needed in the area to confirm results.